Green jobs: Barriers and drivers in the EU - Justas Streimikis; Ladislav Mura; Grigorios L. Kyriakopoulos; Arturas Simanavicius; Milica Delibaci (Contemporary Economics, 2024)
There are many barriers to green job expansion in the EU linked to cultural, economic barriers, organizational, political, technological technical, social, and behavioral barriers. The main drivers of green job creation include social norms and rules, governance policies, cultural values, demographic data, socio-economic inclusion, technical, and technological elements, etc. The aim of this paper is to analyze barriers and drivers that can influence green job expansion. The case study on green jobs expansion in the EU is provided based on statisti- cal data from EUROSTAT. The policies and measures aiming to cope with barriers to green job expansion and support drivers of these processes are recommended for EU countries based on research conducted.
Keywords: H30; P18; Q20; Q30; 330; transformative changes; carbon neutral society; barriers; drivers; policies; and measures